2004
DOI: 10.1161/01.hyp.0000114601.30306.bf
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant D 1 and D 3 Dopamine Receptor Transregulation in Hypertension

Abstract: Abstract-Dopamine plays a role in the regulation of blood pressure by inhibition of sodium transport in renal proximal tubules (RPTs) and relaxation of vascular smooth muscles. Key Words: receptors Ⅲ dopamine Ⅲ rats Ⅲ hypertension Ⅲ normotension Ⅲ kidney Ⅲ vascular smooth muscle S everal studies have reported that an impaired renal dopaminergic system may contribute to the pathogenesis of hypertension. 1,2 There is increasing evidence for a direct interaction between D 1 -like and D 2 -like receptors in the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 39 publications
0
62
0
Order By: Relevance
“…Our previous studies also showed that the D 1 receptor-mediated stimulation on D 3 receptor expression is impaired in SHR RPT cells. 42 We also found that the costimulation of D 1 -like and D 3 receptors led to additive vasorelaxation in WKY rats but not in SHRs. 42 Luippold et al 47 reported that both expression and function of the renal D 3 receptor are impaired in salt-sensitive Dahl rats as compared with salt-resistant Dahl rats.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Our previous studies also showed that the D 1 receptor-mediated stimulation on D 3 receptor expression is impaired in SHR RPT cells. 42 We also found that the costimulation of D 1 -like and D 3 receptors led to additive vasorelaxation in WKY rats but not in SHRs. 42 Luippold et al 47 reported that both expression and function of the renal D 3 receptor are impaired in salt-sensitive Dahl rats as compared with salt-resistant Dahl rats.…”
Section: Discussionmentioning
confidence: 50%
“…42 We also found that the costimulation of D 1 -like and D 3 receptors led to additive vasorelaxation in WKY rats but not in SHRs. 42 Luippold et al 47 reported that both expression and function of the renal D 3 receptor are impaired in salt-sensitive Dahl rats as compared with salt-resistant Dahl rats. 3,47 In contrast, these investigators did not find a defective response to the intravenous infusion of a D 3 receptor agonist [R(ϩ)-7-hydroxydipropylaminotetralin] in SHRs.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The AT 1 receptor can also form complexes with the b2 adrenergic receptors, and it is possible to effectively block dual receptor signaling using only a single receptor antagonist (Barki-Harrington et al, 2003). The AT 1 receptor also coimmunoprecipitates with the epidermal growth factor receptor (EGFR); dopamine D1, D3, and D5; and the endothelin B receptors (Zeng et al, 2003a(Zeng et al, ,b, 2005a(Zeng et al, ,b, 2006Olivares-Reyes et al, 2005).…”
Section: E Signalingmentioning
confidence: 99%
“…For example, the development of hypertension, regardless of its mechanism, is often the result of an altered renal set point for sodium. In this respect, mutations in sodium channels (21) and/or defective hormonal responses (22), as well as abnormal function and regulation of Na ϩ ,K ϩ -ATPase by dopamine, have been described (23,24).…”
Section: Salt and Water Transport: Pathophysiologic Impact Within Thementioning
confidence: 99%